THE ROLE AND SIGNIFICANCE OF GAME IN EARLY DEVELOPMENT OF PRESCHOOL CHILDREN - Tanja, Nedimović; Euđen, Cinc; Jelena, Prtljaga (PUPIL: International Journal of Teaching, Education and Learning, 2017)
Man develops and changes from conception through end of its life cycle. Under development we mean series of quantitative and qualitative changes over time period that can be progressive or regressive (but not pathological – those changes are not subject of developmental psychology). Preschool age is period in which whole series of developmental changes occur. Child play in early childhood is dominant daily activity. Music game and the increasing attention paid to it has been a result of changing the concept of musical upbringing and education in broader professional circles. In the same time it is beyond dispute that learner-specific features are significant factors of foreign language learning and teaching. Pleasure, which is a consequence of play, is the only conscious reason of why child engage in play. Child play is the activity that is in the same time game and work because play affects all aspects of child development (senso-motor, cognitive, emotional, moral, social, as well as speech development). In social view, play is preparation of child for life in society with others. Also, we will include classification of preschool children games, in accordance with their level of cognitive development and level of social inclusion.